Diaphragm ultrasound to evaluate the antagonistic effect of sugammadex on rocuronium after liver surgery in patients with different liver Child-Pugh grades: study protocol for a prospective, double-blind, non-randomised controlled trial. Issue 2 (1st February 2022) - Sun, Shujun; Sun, Yan; Chen, Rui; Yao, Chunlin; Xia, Haifa; Chen, Xiangdong; Lin, Yun; Yao, Shanglong
Abstract : Introduction: The use of muscle relaxants is an indispensable in the general anaesthesia but is prone to accidents, which are often related to residual muscle relaxant. Therefore, how to timely and effectively eliminate the residual effect of muscle relaxants after surgery has become an urgent clinical problem. Rocuronium is a non-depolarising muscle relaxant that is primarily metabolised by the liver. Patients with liver dysfunction can affect the metabolic process of rocuronium, thereby delaying the recovery of muscle relaxation. Sugammadex (SUG) is a novel-specific antagonist of aminosteroidal muscle relaxants, which can effectively antagonise muscle relaxants at different depths. However, whether liver dysfunction affects the antagonistic effect of SUG against rocuronium has not been reported. Therefore, we hypothesise that with the increase of patients' liver Child-Pugh grade, the recovery time of rocuronium antagonised by the same dose of SUG after surgery will be prolonged, and the incidence of muscle relaxation residual will be increased in the short term. Methods and analysis: This study is a prospective, double-blind, low-intervention, non-randomised controlled clinical trial involving 99 patients with American Society of Anesthesiologists (ASA) Ⅰ–Ⅲ, body mass index 18.5–24.9 kg/m 2, who will undergo laparoscopic radical resection of liver cancer under general anaesthesia in the Union Hospital, Tongji Medical College, Huazhong University of Science and Technology. Ultrasonography will be applied to monitor the change rate of diaphragm thickness at different time after extubation to evaluate the occurrence of residual muscle relaxant, which indirectly reflects the dose–effect relationship of SUG antagonising against rocuronium in patients with different liver Child-Pugh grades preoperatively. Ethics and dissemination: The protocol was reviewed and approved by the Medical Ethics Committee of Union Hospital Affiliated to Tongji Medical College of Huazhong University of Science and Technology (UHCT21012). The findings will be disseminated to the public through peer-reviewed scientific journals. Trial registration number: NCT05028088 .